Respond to this Question
Similar Questions

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE
asked by cv on October 21, 2013 
Geometry
A parabola has a focus of F(2,8.5) and a directrix of y=9.5. The point P(x,y) represents any point on the parabola, while D(x,9.5) represents any point on the directrix. Maria was asked to use the distance formula to write an
asked by lilbaby on December 4, 2018 
Chemistry
In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
asked by Haley on April 7, 2015 
Algebra help
f(x)=x^34x^2x+4 How do I find the xintercept for this? This is from my book: step 1: 0=x^34x^2x+4 step 2: 0=x^2(x4)+(1)(x4) step 3: 0=(x^21)(x4) I know how to solve once I get to step 3, but in step 2, I don't know what
asked by Claure on June 16, 2009 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
Math
In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by 1, xy= y^2. Step 4: Adding x^2 to both sides, x^2xy=x^2y^2. Step 5: Factoring, x(xy)=(x+y)(xy).
asked by Hannah on February 1, 2016 
Quick math help
In which step below does a mistake first appear in simplifying the expression? 0.5(12c+6)3(c+4)+10(c5) Step 1: 6c+33(c+4)+10(c5) Step 2: 6c+33c12+10(c5) Step 3: 6c+33c12+10c50 Step 4: 7c41 Please help me!!! Thank
asked by Anonymous on December 11, 2013 
math
Tom is showing his work in simplifying (5.2 – 8.5) – 0.5 + 6.8. In which step did Tom make an error? Step 1:: (5.2 – 8.5) – 0.5 + 6.8 Step 2: 5.2 + (–8.5 – 0.5) + 6.8 (distributive property) Step 3: 5.2 – 9 + 6.8
asked by Gerold Humpfrey the Third on May 16, 2019